Acute toxicity and biochemical effects of azinphos methyl in the amphipod Hyalella curvispina - Anguiano, Olga L. (2014)
We evaluated the acute toxicity and biochemical effects of the organophosphorus pesticide azinphos methyl (AM) in the amphipod Hyalella curvispina that inhabits ponds and irrigation channels of an intensive fruit-producing region in Rio Negro and Neuque´ n valley, North Patagonia, Argentina. The analysis by nonlinear regression of data from the 96 h-acute toxicity tests indicated the coexistence of two subpopulations of H. curvispina with different susceptibilities to AM. The 96 h-LC50 for the resistant subpopulation (166 6 56 lg/L) was 216-fold higher than the 96h-LC50 value for the susceptible one (0.77 6 1.33 lg/L).The two subpopulations could not be distinguished based on the biochemical measurements in control amphipods. Cholinesterase activity was significantly inhibited in AM-exposed amphipods in a concentration-dependent manner. The IC50 value obtained after 96 h of exposure (2.18 6 1.95 lg/L) was significantly lower than the 48 h-IC50 value (29.6 6 17.4 lg/L). Carboxylesterase activity was significantly inhibited after 48 h of exposure to 12.5 and 62.5 lg/L AM (inhibition, 51%). This enzyme was thus able to protect cholinesterase from inhibition at 12.5 lg/L AM. Reduced glutathione and catalase showed a significant increase after 24 h of exposure as an adaptive response to AM, whereas glutathione S-transferase activity was not significantly modified. The analysis of species sensitivity distribution showed that both subpopulations of H. curvispina were more tolerant to AM than most amphipod species, and that the susceptible subpopulation was more sensitive to AM than the other local aquatic species analyzed. The maximum concentration of AM in drainage water within the fruit-producing area reported by other studies would affect most of the amphipod species (99%) and also a 44% of local aquatic ones. The results obtained in this study point out the usefulness of including amphipods like H. curvispina in ecotoxicity studies and monitoring programs to perform pesticide risk assessments.